Costs and acceptability of simplified monitoring in HIV-suppressed patients switching to dual therapy: the SIMPL’HIV open-label, factorial randomised controlled trial (Swiss Medical Weekly, 2024)
BACKGROUND: Clinical and laboratory monitoring of patients on antiretroviral therapy is an integral part of HIV care and determines whether treatment needs enhanced adherence or modification of the drug regimen. However, different monitoring and treatment strategies carry different costs and health consequences.MATERIALS AND METHODS: The SIMPL’HIV study was a randomised trial that assessed the non-inferiority of dual maintenance therapy. The co-primary outcome was a comparison of costs over 48 weeks of dual therapy with standard antiretroviral therapy and the costs associated with a simplified HIV care approach (patient-centred monitoring [PCM]) versus standard, tri-monthly routine monitoring. Costs included outpatient medical consultations (HIV/non-HIV consultations), non-medical consultations, antiretroviral therapy, laboratory tests and hospitalisation costs. PCM participants had restricted immunological and blood safety monitoring at weeks 0 and 48, and they were offered the choice to complete their remaining study visits via a telephone call, have medications delivered to a specified address, and to have blood tests performed at a location of their choice. We analysed the costs of both strategies using invoices for medical consultations issued by the hospital where the patient was followed, as well as those obtained from health insurance companies. Secondary outcomes included differences between monitoring arms for renal function, lipids and glucose values, and weight over 48 weeks. Patient satisfaction with treatment and monitoring was also assessed using visual analogue scales.RESULTS: Of 93 participants randomised to dolutegravir plus emtricitabine and 94 individuals to combination antiretroviral therapy (median nadir CD4 count, 246 cells/mm3; median age, 48 years; female, 17%),patient-centred monitoring generated no substantial reductions or increases in total costs (US$ –421 per year [95% CI –2292 to 1451]; p = 0.658). However, dual therapy was significantly less expensive (US$ –2620.4 [95% CI –2864.3 to –2331.4]) compared to standard triple-drug antiretroviral therapy costs. Approximately 50% of participants selected one monitoring option, one-third chose two, and a few opted for three. The preferred option was telephone calls, followed by drug delivery. The number of additional visits outside the study schedule did not differ by type of monitoring. Patient satisfaction related to treatment and monitoring was high at baseline, with no significant increase at week 48.CONCLUSIONS: Patient-centred monitoring did not reduce costs compared to standard monitoring in individuals switching to dual therapy or those continuing combined antiretroviral therapy. In this representative sample of patients with suppressed HIV, antiretroviral therapy was the primary factor driving costs, which may be reduced by using generic drugs to mitigate the high cost of lifelong HIV treatment.Trial registration: ClinicalTrials.gov NCT03160105.